Ascertaining the mechanistic etiology of COVID-associated glomerulonephritis: a systematic review - Coyne, Brendan M.; Ito, Danielle; Tariq, Anam; Lew, Susie Q.; Kopp, Jeffrey; Vinales, Patricia Centron; Malik, Fahim; Gipson, Patrick E.; Nobakht, Ehsan (Frontiers in Medicine, 2025)
BackgroundSince its first reported case in December 2019, COVID-19 disease, caused by severe acute respiratory coronavirus 2 (SARS-CoV-2), evolved into a major pandemic throughout the world. Although COVID-19 is most often characterized as a respiratory pathology, there are also extensive reports of renal complications, such as glomerulonephritis (GN). However, the precise nature of COVID-associated glomerulonephritis (COVID-GN) has yet to be fully understood. This review seeks to elucidate COVID-GN pathophysiology by conducting an exhaustive systematic review.MethodsHerein, we compare the different GN subtypes associated with COVID-19 in the literature. We also review the cytokines, antibodies, and genes most implicated in COVID-GN.ResultsThe GN subtype with the highest number of cases associated with COVID-19 infection was focal segmental glomerulosclerosis, specifically the collapsing morphology. Meanwhile, the highest number of cases associated with COVID-19 vaccination was IgA nephropathy. The most prevalent mechanism in the literature for COVID-GN involves a cytokine storm, which may be accompanied by immune complex deposition.DiscussionBoth infection and vaccination from SARS-CoV-2 can induce robust CD4+ T cell responses promoted by an IL-6 amplifier loop of inflammation. This immune response is likely further enhanced by interactions with complement systems and the renin-angiotensin-aldosterone system (RAAS). SARS-CoV-2-mediated pathways of both direct cytotoxicity and stimulation of polyclonal immunoglobulin may converge to cause glomerular inflammation and injury. Further investigation of these inflammatory pathways may provide insight into COVID-19 pathophysiology, treatment, and long-term outcomes.